Evolution Characteristics of Urban Heat Island Circulation for Loess Tableland Valley Towns - Zhuolei Yu; Yi Wang; Jukun Wang; Xiaoxue Wang; Songheng Wu (Buildings)
Urban heat island circulation (UHIC) determines the wind and thermal environments in urban areas. For Loess Tableland valley towns, the evolution characteristics of the UHIC over this negative terrain are not well understood, and therefore, it is important to investigate the evolution characteristics. A city-scale computational fluid dynamics (CSCFD) model is used, and simulation results are validated by the water tank experiment. The evolution process over such negative terrain can be divided into transient and quasi-steady stages, and in the transient stage, the airflow pattern evolves from thermal convection to city-scale closed circulation, while that in the quasi-steady stage is only city-scale closed circulation. In order to further reveal the characteristics of city-scale closed circulation, the sensitivities of different factors influencing the start time, outflow time, mixing height and heat island intensity are analyzed, and the most significant factors influencing these four parameters are urban heat flux, slope height, slope height, and potential temperature lapse rate, respectively. Finally, the dimensionless mixing height and heat island intensity for the valley town increase by 56.80% and 128.68%, respectively, compared to those for the flat city. This study provides guidance for the location and layout of built-up areas in the valley towns.